Akhlak Kepada Kedua Orang Tua Presfektif Hadis - Harlinda; Arifuddin; Erwin Hafid (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research is entirely in the nature of library research. This research was conducted in the literature by collecting primary data from books that discuss morality to both parents from a hadith perspective. Data processing was carried out qualitatively, considering that the data encountered is descriptive in the form of verbal statements. The results of this study indicate that Islam highly values filial piety to parents. However, being devoted to parents has limits, that is as long as the act of filial piety does not violate the provisions outlined by Allah SWT, both of which have been explained in the Al-Qur'an and Hadith. For example, if a parent forces a child to commit shirk or commit a crime, the parent's order must be opposed, but remember, it must be in a good way so that they are not offended. Birrul walidain or devoted to both parents has a special position in Islamic teachings. The matter of filial piety to parents has been regulated both in the Qur'an and Hadith. The command to do good to parents was placed by Allah SWT in the Qur'an directly after the command to worship only Him, solely or after the prohibition of associating partners with Him, and there is also a hadith that the pleasure of Allah depends on the pleasure of parents, good deeds. what Allah loves most is serving your parents, doing good to your mother is more important, serving both parents is the way to heaven.